(untitled) (International Journal of Food and Nutritional Sciences, 2022)
All living things, including animals, plants, people, and agriculture, depend on water as a basic resource. Water also has an impact on the nation’s industrial and commercial sectors. Kolhapur, sometimes referred to as southern region of Maharashtra. The studied area’s physical environment, the presence of the Sahyadri highlands, foothills, plains and shifting climatic conditions all contributed to the varied and irregular pattern of rainfall distribution